Effects of Communities That Care on Males' and Females' Drug Use and Delinquency 9 Years After Baseline in a Community‐Randomized Trial. Issue 3 (16th September 2015) - Oesterle, Sabrina; Hawkins, J. David; Kuklinski, Margaret R.; Fagan, Abigail A.; Fleming, Christopher; Rhew, Isaac C.; Brown, Eric C.; Abbott, Robert D.; Catalano, Richard F.
Abstract : Abstract: This study tested sustained effects of the Communities That Care (CTC) prevention system on health‐risking behaviors 9 years after baseline in a community‐randomized trial involving 24 towns in seven states. Earlier analyses found sustained effects on abstinence from drug use and delinquency through Grade 12 in a panel of fifth graders. At age 19, 91 % (n = 3986) of the living panel completed the survey. Data were analyzed using generalized linear mixed models. The prevalence of lifetime and current substance use and delinquency were the primary outcomes. Secondary outcomes included substance use disorders, major depression, suicidality, educational attainment, and sexual risk behaviors. CTC had a significant overall effect across lifetime measures of the primary outcomes for males, but not for females or the full sample, although lifetime abstinence from delinquency in the full sample was significantly higher in CTC communities (ARR = 1.16). Males in CTC communities also continued to show greater lifetime abstinence from cigarette smoking (ARR = 1.22). CTC did not have a sustained effect on current substance use and delinquency nor did it improve the secondary outcomes at age 19 for either gender. Communities using CTC may need to extend their prevention planning to include the high school years to sustain effects on drug use and delinquency beyond high school for both genders. Trial Registration: ClinicalTrials.gov identifier: NCT01088542.